Reforming the UK's citizenship test : building bridges, not barriers - Brooks, Thom (Bristol shorts research., 2022)
Thom Brooks draws on first-hand experience and interviews with key figures including past Home Secretaries to expose the UK's Citizenship test as ineffective and a barrier to citizenship. This accessible guide offers recommendations for transforming the citizenship test into a 'bridge to citizenship' which fosters greater inclusion and integration.